It's legal but it ain't right : harmful social consequences of legal industries - Passas, Nikos; Goodwin, Neva R. (Evolving values for a capitalist world., 2004)
Many U.S. corporations and the goods they produce negatively impact our society without breaking any laws. We are all too familiar with the tobacco industry's effect on public health and health care costs for smokers and nonsmokers, as well as the role of profit in the pharmaceutical industry's research priorities. It's Legal but It Ain't Right tackles these issues, plus the ethical ambiguities of legalized gambling, the firearms trade, the fast food industry, the pesticide industry, private security companies, and more. Aiming to identify industries and goods that undermine our societal values and to hold them accountable for their actions, this collection makes a valuable contribution to the ongoing discussion of ethics in our time.